The variability of competitive performance and pacing strategies in different rounds of the 400 m and 800 m freestyle swimming races at the 2017–2024 World Swimming Championships - Fang, Junhui; Li, Yunpeng; Cheng, Yan (Frontiers in Sports and Active Living, 2024)
Introduction This study aims to analyze the competitive performance and pacing strategies (PS) of medalists and non-medalists in different rounds of the 400 m and 800 m freestyle at the World Swimming Championships. Method The 2017–2024 World Swimming Championships and 161 elite swimmers were selected. First, intra-athlete coefficients of variability (CVs) were evaluated using linear mixed effects modeling and changes in competitive performance (Δ); second, descriptive statistics of position lap time; finally, a computer algorithm was used to obtain PS, then a two-way ANOVA was performed. Result (i) The PS was effective in 87.5% of the swimmers in the finals compared to the heats (CVs > 0.5%), but 73.8% of the males and 86.8% of the females showed an improvement in performance prior to the finals (Δ < 0); (ii) Gold medalists had an average position no lower than the top 2 and established themselves in the top 3 positions more than 90% of the time, aiming to remain in the top 3 until the final 100 m if they were to win a medal; (iii) The female swimmers in 400 m were more in the heats utilize the inverted-J (race velocity change curve profile as inverted-J), men for the fast-start-even, in the final, female remain the inverted-J, men change to the U-shaped (race velocity change curve profile as U-shaped), and in the 800 m, the swimmers were unified adopt the U-shaped. Discussion The elite swimmers who qualified for the finals performed better in the heats and semifinals because their PS were more effective. Others, however, did not have a chance to reach the finals because their PS efficiency was lower, and their competitive performance improved less or even regressed.